Persepsi dan Ekspektasi Masyarakat Terhadap Konflik Dengan Ptpn V di Desa Senama Nenek Kecamatan Tapung Hulu Kabupaten Kampar - Nur Imam Taufik; Eri Sayamar; kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The Purpose of study to determine the perceptions and expectations of society to conflict with the villagers of PTPN V Senama Nenek in the village Senama Nenek, District of Tapung Hulu, Regency of Kampar. To determine the respondents used key informants and samples. Sampling method by purposive sampling. A total of 30 people were sampled with consideration to be in the same area, the criteria of the sample in this study is that people know about conflictvillagers Senama Nenek with PTPN V data retrieval technique that is used is the survey method. The data have been obtained in the field of Qualitative Descriptive analyzed. Then conducted with respondents from making any distribution tabulation variables studied. Variable to describe people's perceptions and expectations of conflict used a Likert Scale.Research results show that: (1) Public perception of conflict understanding gentleness quite understand the category measured from the perception of the problem of understanding conflict, understanding the perception of conflict actors purposes of understanding and perception of the conflict actors; (2) the conflict gentleness community expectations on high expectations measured categories of goals, pathways thingking and agency thingking.   Keywords: Expectations, conflictandperceptions